A software solution for point counting. Petrographic thin section analysis as a case study - Larrea, Martin Leonardo (2014)
In the field of geology, as in many other fields, a common problem is the analysis of 2D sections. An example of this is the petrographic study of rock samples, i.e., the quantification of its mineral components and the percentages of each phase present in it. Conventionally, this quantification has been determined by point counting performed on thin sections. Although point counting is very time consuming, it is of common use in several domains including geology, biology, medicine, and materials sciences, among others. Point counting in thin sections is normally conducted through mechanical or electromechanical devices attached to a microscope; such devices are very expensive, offer limited functionality, and are very time consuming. In this contribution, we introduce an interactive visualization application called Rock.AR that reduces the amount of time required to apply this technique and simplify its work flow. It provides visual tools like distortion techniques, overview + detail, and statistics to assist the technique. A comparison between this application and similar tools through users´ experiences is provided. We compare the time it takes to complete a session of point counting and the tools´ usability.